الطريقة المباشرة في تعليم اللغة الإنجليزية - Yerni Amir (Institut Agama Islam Negeri (IAIN) Metro, 2017)
The Direct Method has been populer since the Grammar Translation was not very effective in preparing students to use the Target Language communicatively. No Translation is allowed is one of the characteristic of The Direct Metdhod. The student should associate meaning and the Target sLanguage directly. In order to do this , when the teacher introduces a new Target Language word or phrase , he/she demonstrates its meaning through the use of realia, pictures, or teacher as a model. He never translates it into the students’ native language. In order to do this successfully, students should learn to think in Target Language